TOURISM STRATEGY MANAGEMENT IN POST ECONOMIC RESILIENCE COVID-19 PANDEMIC (STUDY ON SITU GEDE TASIKMALAYA TOURISM OBJECT) - Sumali, Soni; Triani, Tuti; Karmila, Mila (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research aims to analyze the competitiveness of the Tasikmalaya Regency tourism sector and to find out the factors that determine and influence competitiveness as well as strategies that can be taken to increase the competitiveness of the tourism sector. The data used is secondary and primary data, namely GRDP data for Tasikmalaya Regency in 2017-2021 and supporting tourism-related data as well as in-depth interviews with the Tasikmalaya Regency Tourism, Youth and Sports Department (DISPARPORA). In this research, the Porter's Diamond model approach was carried out which was calculated using a composite index and quadrant analysis. The results of the shift share analysis show that in 2017-2021 the tourism sector experienced rapid growth and was able to compete with the same sector at the national level. In line with the shift share results, the results of analysis using the Porter's diamond model approach show that the Tasikmalaya Regency tourism sector has quite good competitiveness compared to its comparison provinces. Factors that have advantages in determining competitiveness are related supporting industry factors and factor conditions. Kor key: Competitiveness; Tourist; Competitiveness Monitor; Porter's Diamond.